2018
DOI: 10.5205/1981-8963-v12i1a23520p102-111-2018
|View full text |Cite
|
Sign up to set email alerts
|

Sentimentos vivenciados por mulheres ao receberem o diagnóstico de câncer de mama

Abstract: Objective: to understand the feelings experienced by women when they are diagnosed with breast cancer. Method: qualitative, descriptive and exploratory study, with 13 women assisted by a social assistance organization. The production of the data occurred through an audio interview recorded and guided by the question: what were the feelings experienced when the diagnosis of breast cancer was received? Data analysis was based on the Content Analysis technique. Results: upon receiving the diagnosis of breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 4 publications
(10 reference statements)
1
11
0
8
Order By: Relevance
“…This disorganization caused by the illness process is reflected as a difficulty for young women to play the roles that permeate their social interactions, from the role of mother to professional. [1][2][3] For women in this age group who are entering the professional career, the work was associated with concrete and emotional aspects, such as independence, autonomy, personal satisfaction, career success as well as financial supply and increased social relationships. 4 In this sense, due to improvements in the health system there are a growing number of cancer survivors and it is noted that almost one third of people with cancer are at an active age.…”
Section: Introductionmentioning
confidence: 99%
“…This disorganization caused by the illness process is reflected as a difficulty for young women to play the roles that permeate their social interactions, from the role of mother to professional. [1][2][3] For women in this age group who are entering the professional career, the work was associated with concrete and emotional aspects, such as independence, autonomy, personal satisfaction, career success as well as financial supply and increased social relationships. 4 In this sense, due to improvements in the health system there are a growing number of cancer survivors and it is noted that almost one third of people with cancer are at an active age.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that receiving the diagnosis triggers emotional feelings of unreality and even confrontations with the idea that death is about to happen. 14 In this scenario, families appear as a source of support, in order to bring greater quality of life and incentive in the search for strength to face the disease. 15 Such situations can be identified in the statements of Tulipa, Rosa and Violeta:…”
Section: Family Behavioral Changesmentioning
confidence: 99%
“…Essa fala afirma a busca pela atenção primária, mas a continuidade do tratamento fica com déficit, e pela necessidade da urgência, o serviço particular está mediano a entrada no tratamento definido pelo SUS, seja cirúrgico, quimioterapia ou radioterapia. As falas supracitadas corroboram com colocações descritas em estudos 12 onde diz: um dos sentimentos vivenciados pelos pacientes em tratamento quimioterápico é a do sofrimento físico. A dor física e a fragilidade em que se encontram essas pessoas revelam como é difícil conviver com uma situação de adoecimento, cujo tratamento é agressivo.…”
Section: "Estou Aqui Para Me Tratar Se Deus Quiser Vou Conseguir Superar Descobri Que Estou Com Câncer De úTero Eu Sempre Fazia Exames Tounclassified